Blue-green light treatment enhances the quality and nutritional value in postharvest Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Ruixing Zhang; Qianqian He; Qiming Pan; Yizhe Feng; Yu Shi; Gaizhen Li; Yi Zhang; Yulin Liu; Abid Khan (Food Chemistry: X)
Chinese cabbage is a vital while perishable leafy vegetable. Blue-green light combined treatment was found to be better to retain high nutritional value in Chinese cabbage than blue or green monochromatic light treatments by increasing the contents of soluble protein, indol-3-ylmethyl (I3M), flavonoids, total phenols and carotene. Gene expression study further revealed that blue-green light treatment increased the expression of biosynthetic genes in the metabolic pathways of glucosinolates (BrCYP79B2, BrIGMT1), flavonoids (BrCHS.1, BrF3H, BrCHI) and carotenoids (BrPSY1, BrLCYB, BrLCYE, BrVDE), as well as the light signal master regulator gene BrHY5.2. In addition, the blue-green light treatment up-regulated the activities of antioxidant enzymes, as well as 2,2-diphenyl-1-picrylhydrazyl and ferric-reducing antioxidant power activities, while reducing the levels of superoxide anion, hydrogen peroxide (H2O2), polyphenol oxidase (PPO) activity and malondialdehyde (MDA). Overall, our findings confirmed that blue-green light treatment can effectively enrich the nutritional value and prolong the shelf life of Chinese cabbage.